Disain Ergonomik dengan Catia Model - Hidayat, Rachmad; Adil, Malikul (Universitas Trunojoyo Madura, 2008)
Ergonomic Design is the design tooptimizing the relationship between technology and human error. Ergonomic design are use for optimizing efficiency and safety. It takes in account relevan human characteristic of the operator and the design such system to te compatible with those characteristic. Ergonomic design are widely use in industries where occupational health and safety are considered as vital contributors to productivity and competitiveness. From the observation of the process, we can see that the operators isgreatly exposed to several manual matrial handling rish factors. Lijt/fo wer analysis and RULA assessment are performed in assessing the degree of discomfort present in the work process. Then tree the new design are proposed as an ergonomic intervention. These the new design are analyzed to measure the erformance of each new design. This analysis is performed using CATIA. This technique can be applied by designer to improve the working conditions, wherw machine operators are experiencing discomfort and ergonomic intervention is immediately required.